(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Foreign Direct Investment (FDI) plays an extraordinary and growing role in global business. It can provide new technologies, capital, processes, products, organizational technologies and management skills and as such can provide a strong impetus to economic development. New FDI policy in India will allow 51 percent in multi brand retail and 100 percent in single brand retail, opening the door to global players. This policy will bring more demand from overseas give more confidence to mail dealers. FDI refers to capital inflows invested in to enhance the production capacity of the economy. In the post liberalization era, organized retail has grown exponentially.